Protecting the Rights of Publicity of Michael Jordan, Pele, and Muhammad Ali - Sperling, Frederick J. (The Columbia Journal of Law & the Arts, 2019)
It is a pleasure to have a chance to speak with you this afternoon. I would like to talk with you about several cases that I brought involving misappropriation of the rights of publicity of Michael Jordan, Pele, and Muhammad Ali.